2019
DOI: 10.1002/lary.28276
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced laryngeal obstruction (EILO) in children and young adults: From referral to diagnosis

Abstract: Objective: To identify different presentations, referral patterns, comorbidities, and laryngoscopy findings in children and young adults with exercise-induced laryngeal obstruction (EILO).Methods: We performed a retrospective chart review of 112 patients, age <26 years, with EILO between 2013 and 2016. Results: Of the 112 patients who met criteria, 91 were female and 21 were male. Patients were most frequently referred by pulmonologists (60.7%). The majority of patients (93%) participated in organized sports, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 35 publications
1
33
0
1
Order By: Relevance
“…6 Interarytenoid injection and ventricular fold injections have been reported to improve function in some patients. 4,6,7 Using botulinum toxin injection to treat RLD was first described by Grillone et al, Blitzer and Brin, and Brin et al 8,13,14 It has been shown to reduce the quantity and quality of spasms and therefore produce noticeable improvement in breathing. 1 Botulinum toxin takes effect after an average of 43.2 hours, with maximal effect after 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Interarytenoid injection and ventricular fold injections have been reported to improve function in some patients. 4,6,7 Using botulinum toxin injection to treat RLD was first described by Grillone et al, Blitzer and Brin, and Brin et al 8,13,14 It has been shown to reduce the quantity and quality of spasms and therefore produce noticeable improvement in breathing. 1 Botulinum toxin takes effect after an average of 43.2 hours, with maximal effect after 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the most effective treatment of RLD has been botulinum toxin injections into the adductor compartment to affect the lateral cricothyroid muscles and thyroarytenoid muscles 6 . Interarytenoid injection and ventricular fold injections have been reported to improve function in some patients 4,6–7 . Using botulinum toxin injection to treat RLD was first described by Grillone et al, Blitzer and Brin, and Brin et al 8,13–14 It has been shown to reduce the quantity and quality of spasms and therefore produce noticeable improvement in breathing 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunctional breathing is a term describing changes in breathing pattern that result most commonly in dyspnoea (4). Dysfunctional breathing can be viewed in two component parts; a breathing pattern component and an upper airway component.…”
Section: Dysfunctional Breathingmentioning
confidence: 99%
“…Shortness of breath is the most common presenting complaint ( 4 ). It may be precipitated by exertion and is often worse with increasing intensity and duration of exercise, however it can occur at rest.…”
Section: Diagnosismentioning
confidence: 99%